Love comes calling - Mitchell, Siri L., 1969- (Bethany House, a division of Baker Publishing Group, 2014)
"In 1920s Boston, with her job on the line and her heart all a-muddle, aspiring actress Ellis Eton discovers what might be her role of a lifetime"--